Comparison of Pain Intensity in Post-Operating Wound Treatment Using Distraction and Relaxation Techniques at Imelda Pekerja Indonesia General Hospital Medan City - Manurung, Nixson (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The purpose of this study was to determine the intensity of pain in postoperative wound care using distraction and relaxation techniques at Imelda Workers' Hospital in Medan 2018. This type of research was quantitative research and the research design used was quasi-experimental before and after treatment and the therapy given was distraction therapy and relaxation therapy. The study was carried out in the postoperative inpatient ward of Imelda Indonesian Workers Hospital Medan from June to August 2018. The results of this study were: 1. The average pain intensity before distraction techniques was moderate (NRS 5.11) while the average intensity of pain before relaxation techniques was in moderate pain (NRS 5.38). 2. The average pain intensity after the distraction technique was on the moderate pain scale but decreased in scale (NRS 3.11) while the average pain intensity after the relaxation technique was on moderate pain but the scale decreased (NRS 4.192). 3. There are differences in the effectiveness of distraction and relaxation techniques on changes in pain intensity of postoperative patients at the Indonesian Migrant Worker General Hospital Imelda Medan in 2018 (p-value 0.001).Abstrak: Tujuan penelitian ini adalah untuk Mengetahui intensitas nyeri dalam perawatan luka pasca operasi dengan menggunakan tehnik distraksi dan relaksasi di RSU Imelda Pekerja Indonesia Medan 2018. Jenis penelitian ini adalah penelitian kuantitatif dan desain penelitian yang digunakan adalah eksperimen semu sebelum dan sesudah perawatan dan Terapi yang diberikan adalah terapi distraksi dan terapi relaksasi. Penelitian dilaksanakan di ruang rawat inap pasca operasi Rumah Sakit Imelda Tenaga Kerja Indonesia Medan pada bulan Juni sampai Agustus 2018. Hasil penelitian ini adalah: 1. Rata-rata intensitas nyeri sebelum dilakukan teknik distraksi pada nyeri sedang (NRS 5.11) sedangkan rata-rata intensitas nyeri sebelum teknik relaksasi berada pada nyeri sedang (NRS 5,38). 2. Rata-rata intensitas nyeri setelah teknik distraksi berada pada skala nyeri sedang tetapi mengalami penurunan skala (NRS 3.11) sedangkan rata-rata intensitas nyeri setelah teknik relaksasi berada pada nyeri sedang tetapi skalanya mengalami penurunan (NRS 4.192). 3. Terdapat perbedaan efektivitas teknik distraksi dan relaksasi terhadap perubahan intensitas nyeri pasien post operasi di Rumah Sakit Umum Tenaga Kerja Indonesia Imelda Medan Tahun 2018 (p value 0,001)